Evidence for lectin activity of a plant receptor-like protein kinase by application of neoglycoproteins and bioinformatic algorithms - André, Sabine; Siebert, Hans-Christian; Nishiguchi, Mitsuru; Tazaki, Kiyoshi; Gabius, Hans-Joachim (Biochimica et biophysica acta, 2005)
Detection of genes for putative receptor-like protein kinases, which contain an extracellular domain related to leguminous lectins, in plant genomes inspired the hypothesis that this part acts as sensor. Initial support for this concept came from proof for protein kinase activity. The next step, focusing on the protein of lombardy poplar ( Populus nigra var. italica), is scrutiny for lectin activity. Consequently, we first pinpointed sets of high-scoring sequence pairs by extensive databank search. The calculations resulted in P-values in the range from 10 −14 to 10 −18 exclusively for leguminous lectins, the Pterocarpus angolensis agglutinin being frontrunner with P = 3 × 10 −18 and thus most suitable template for modeling. The superimposition of the two folds gave notable similarity in the region responsible for binding carbohydrate and Ca 2+/Mn 2+-ions. Binding activity toward carbohydrates was detected by assaying a panel of (neo)glycoproteins as polyvalent probes, especially for α- l-rhamnose and glycans of asialofetuin. It was strictly dependent on Ca 2+-ions, enhanced by Mn 2+-ions and reached a K D-value of 34.3 nM for the neoglycoprotein with rhamnose as ligand. These results give further research direction to define physiological ligands, plant/bacterial rhamnose-containing saccharides and rhamnose-mimetic glycans or peptides being potential candidates.